Kontribusi Keaktifan Siswa dan Fasilitas Belajar Terhadap Motivasi Siswa dan Dampaknya Pada Hasil Belajar Matematika Siswa SMP Negeri Surakarta Tahun 2016/2017 - Saputri, Nunung Pratmulia, Drs. Slamet HW, M.Pd (2016)
The purpose of this study is: (1) to examine the contribution of activity of students, learning on the students motivation, (2) to examine the contribution of student motivation for learning outcomes mathematics, (3) to examine the contribution of activity of students, learning the learning outcomes of mathematics indirectly through motivation students. This research includes quantitative research path analysis. There are three variables in this study is the dependent variable is the result of learning mathematics, intervening variable is motivation students and independent variables is a student activity and learning facilities. The population in this study were students of class VIII Semester Odd SMP Negeri 12 Surakarta Academic Year 2016/2017. Samples taken as many as 69 students with proportional random sampling. The data collection technique with questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability test. Analysis using path analysis, requirements analysis previously conducted trials. The results of this study are: (1) there was a contribution activity of students, learning on the students motivation. It is based on the results of the analysis of pathways that directly affect the students' active student motivation for DE = 62%, while learning facilities directly influence student motivation for DE = 21.9%, (2) there was a contribution to the student's motivation to learn math results for DE = 35.3%. (3) there was a contribution activity of students, learning the mathematics learning outcomes indirectly through student motivation, amounting IE = 18.2%.